Assessment of hepatitis B in high risk people of Gachsaran city, Iran - Khajavian, Mona; Sharifi, Asghar (International Journal of Research in Medical Sciences, 2017)
Background: Hepatitis B virus (HBV) is a major health problem throughout the world. The aim of this study determines the rate of prevalence of molecular and Seroepidemiological hepatitis B infections high risk populations in the Gachsaran city, according to factors such as age, sex, employment status, educational status etc. Methods: In a descriptive and analytical study, blood samples have been collected from 500 high risks individuals, from February 2015 to July 2016 in Gachsaran. The serum samples were tested by ELISA and PCR method was used to confirm the diagnosis. Data were analyzed by SPSS statistical program. Results: HBsAg was detected in 5 out of the 500 individuals, giving an overall prevalence of 1%. All the positive samples were in males. The rate of infection among the individuals with a history of unprotected sexual contact was 8% and was 0% among the individuals who experienced a needle stick. Four out of the five infected persons with hepatitis didn’t receive any vaccination and one of them received only one dose of vaccine. Conclusions: The results showed 1% infection at high-risk groups in the Gachsaran city. Age rising, maleness, unemployment, low educational level and suspicies sexual partners have been the factors of increasing HBV infection prevalence. Full vaccination has a strong and meaningful relationship with hepatitis B in the target groups, which requires all people at risk to be vaccinated completely. Government cooperation to identify and treat injecting drug users and encourage them to follow the preventive methods is beneficial.